THE IMPACT OF PERMEN-KP NO.2 TAHUN 2015 POLICY ABOUT PROHIBITION ON OPERATING CANTRANG (CATCHING TOOL) TO THE ECONOMIC CONDITION OF FISHERMEN IN RAJA BEJAMU VILLAGE,SINABOI DISTRICT, ROHIL, RIAU PROVINCE - Suhendar, Roni; Hamid, Hamdi; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
PERMEN-KP No.2 Tahun 2015 Policy has caused the pros and cons in the society. This study aims to determine how big the impact of these policies on the economy of Fishers as well as the right solution to minimize negative impacts. The research was conducted in February 2016 by 14 Fishermen as respondents in the village of Raja Bejamu, Sinaboi District Riau Province. This study use field survey by interviewing fishermen and their responses before and after the policy. Data shows 21% of fishermen pro and 79% cons with the policy as well as 3 of the 14 fishers claim there is a decrease in their income as a result of the implementation of this rule. The grants to switch catching tool and the grace period is considered to be one of the appropriate solutions to minimize the negative impact. From the results of this study concluded that this policy does not impact to the economy significantly,but there are some obstacles such as the high cost of switching the catching tool and the societies that have been so dependent on the use of cantrang.So it takes a proper solution that the policy should not be a clash between the interests of the government and fishermen.Keywords : Economic Impact, PERMEN-KP No.2 Tahun 2015, Responses of Fishers, Solutions